2005
DOI: 10.1002/j.2162-6057.2005.tb01254.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Creativity to Fluid and Crystallized Intelligence

Abstract: The threshold hypothesis regarding creativity and intelligence suggests that these two constructs are positively correlated except at the higher end of the IQ distribution, where they are unrelated. Much of the support for this hypothesis comes from comparisons of correlations within average and high‐IQ groups. However, a common methodological flaw in these comparisons is that the high IQ group is smaller in variance than the average IQ group. In the present study we equated variances for a better test of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
0
13

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 15 publications
6
51
0
13
Order By: Relevance
“…In assuming the RCPM test to be a measurement related to fluid intelligence, it is possible to verify in the literature studies which found strong correlations with creativity in this type of intelligence, as found in the present study, in making use of the non-case sample (Batey, Chamorro-Premuzic, & Furnham, 2009;Preckel et al, 2006;Sligh, Conners, & Roskos-Ewoldsen, 2005). Nevertheless, as was also found here, studies were observed in the literature which indicated weak correlations between creativity and this type of intelligence (Furnham, Batey, Anand, & Manfield, 2008;Reuter et al, 2005).…”
Section: Discussionsupporting
confidence: 85%
“…In assuming the RCPM test to be a measurement related to fluid intelligence, it is possible to verify in the literature studies which found strong correlations with creativity in this type of intelligence, as found in the present study, in making use of the non-case sample (Batey, Chamorro-Premuzic, & Furnham, 2009;Preckel et al, 2006;Sligh, Conners, & Roskos-Ewoldsen, 2005). Nevertheless, as was also found here, studies were observed in the literature which indicated weak correlations between creativity and this type of intelligence (Furnham, Batey, Anand, & Manfield, 2008;Reuter et al, 2005).…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, Gr would seem to be important, given that creating a good metaphor involves scanning and manipulating stored semantic knowledge, from simple vocabulary to conceptual knowledge of possible topics and vehicles. Some studies have found an important role for Gc in creative thought (e.g., Greengross et al, 2012 andSligh et al, 2005), but for the most part research on intelligence and creativity hasn't examined the range of CHC cognitive abilities. Including Gf, Gc, and Gr in the same study could clarify their unique contributions to creative metaphor production, and it would allow the estimation of a higherorder g factor and its effects.…”
Section: Discussionmentioning
confidence: 99%
“…Wechsler Intelligence Scale for Children). The majority of the contemporary research views intelligence and creativity as distinct constructs that are only weakly related (Batey & Furnham, 2006;Kaufman, 2009;Kim, 2005;Kim, Cramond, & VanTassel-Baska, 2010;Preckel, Holling, & Wiese, 2006;Runco, 2007;Sligh, Conners, & Roskos-Ewoldsen, 2005;Sternberg & O'Hara, 1999). For example, Kim's (2005) meta-analytic study found the mean correlation coefficient between these two traits to be small (r = .17).…”
Section: The Relationship Between Creativity and Processing Speed Formentioning
confidence: 99%